Implicações de estratégias molares/moleculares na Análise Comportamental da Culturai - Da Silva, Felipe Bulzico [UNESP]; Carrara, Kester [UNESP] (My University, 2015)
Since the seminal contributions of Glenn, analysis of sociocultural phenomena in Behavior Analysis has been strongly influenced by assumption of need of a new analysis level. This assumption has favored a molar perspective towards sociocultural phenomena, whose emphasis is on group or social/cultural units identified as object of selection. However, through analyzes that focus on concepts and examples proposed by Glenn, we argue that, on the other hand, those analyzes obscure some relevant variables from the standpoint of a molecular perspective. Furthermore, this article discussed implications that adoption almost exclusive of molar perspectives have had to construction of a behavioral theory of culture.
Implications of molar/molecular strategies for Behavioral Analysis of Culture
Keywords: Behavioral analysis of culture; Ethnography; Molar analysis; Molecular analysis; Radical behaviorism